PECULIARITIES OF DIALOGUES IN PERSONAGES’ INTERGENDER COMMUNICATION (ON THE MATERIAL OF ENGLISH-LANGUAGE MALE AND FEMALE PROSE) - Радкевич, Віта (Current Issues of Foreign Philology, 2021)
The article deals with studying of gender marked issues of inter-gender dialogues taken from contemporary English-language prose fiction written by male and female authors. The topicality of the study is determined by exploiting of the perspectivization principle when the view point is gender determined, thus the investigation is performed along two vectors: the gender issue of the discourse author and the gender of the dialogue participant. The following parameters of inter-gender dialogues are investigated: the profuseness and development of conversational turns with quantitative data, the breach of dialogue structure by interruptions, silence as the reaction to the interlocutor’s conversational turn, as well as quantitative and qualitative features of inter-gender dialogues initiation. The analysis resulted in stating the gender markedness of the given parameters considering both vectors thus showing some distinct qualitative features of inter-gender communication determined by the gender of its participant. The breach of dialogue structure by interruptions is observed largely in female prose. Silence as the reaction to the interlocutor’s conversational turn is a typical characteristics of female communication behaviour. Male personages in discourses created by male authors tend to use statements and various other ways to start their inter-gender dialogues which are difficult to summarize.